A DFT study of H2 adsorption on lithium decorated 3D hybrid Boron-Nitride-Carbon frameworks. (7th June 2019) - Bi, Lan; Yin, Jie; Huang, Xin; Wang, Yunhui; Yang, Zhihong
Abstract: Based on density functional theory (DFT) and first-principles molecular dynamics (MD), a new 3D hybrid Boron-Nitride-Carbon–interconnected frameworks (BNCIFs) consisting of organic linkers with Li decoration is created and optimized. Firstly, Li adsorption behaviors on several BNCx complexes are investigated and compared systematically. The results indicate C substitution of N atom in pure BN layer could improve the metal binding energy effectively. Secondly, the BNC layer (BNCNN ) is chosen to model the frameworks of BNCIFs. The average binding energy of adsorbed Li atoms on BNCIFs is 3.6 eV which is much higher than the cohesive energy of bulk Li and avoids the Li clustering problem. Finally, we study the H2 adsorptions on the Li decorated BNCIFs by DFT. Every Li atom could adsorb four H2 molecules with an average binding energy of 0.24 eV. The corresponding gravimetric and volumetric storage capacities are 14.09 wt% and 126.2 g/L respectively overpassing the published 2020 DOE target. The excellent thermal stability of 160H2 @40Li@BNCIFs is also proved by MD. This nanostructure could be served as a promising hydrogen storage medium at ambient conditions. Graphical abstract: Image 1 Highlights: A 3D hybrid Boron-Nitride-Carbon–interconnected frameworks is modeled. Both Li decoration and C substation of N atom in BN improve hydrogen adsorption. The average binding energy of adsorbed Li atoms (3.6 eV) avoids metal clustering. High hydrogen storage capacity is 14.09 wt% calculated from DFT. High hydrogen volumetric storage capacity reaches 126.2 g/L from DFT.